Evaluation of three implant-supported hybrid prostheses All-on-4® designs. A finite element analysis 3D - Carmona Ramírez, Nora Elena (2020)
Objective. To evaluate stress distribution of three prosthetic designs with the Revitalize Zimmer-Biomet system which follows the All-on-4® concept. Methods. Three 3D models were simulated: R1- Computer-designed and manufactured bar splinting implants, R2- CrCo bar without implant splinting and R3- without internal structure. Each model had four implants (2 anterior straight and 2 posterior distally angled 15º). An axial and oblique load (45º) of 400 N was applied and distributed throughout the prosthesis. Results. The concentration of stress in the peri-implant bone was located in the crestal area for all models with similar values, being slightly higher for R2 (28.74 MPa) and R3 (27.99 MPa). On the prosthesis, the stress increased slightly for the R2 (16.84 MPa) model. In relation to the bar, the highest stress concentration was for R1 (22.16 MPa) and R2 (14.69 MPa) models. Conclusions. There were slight differences between the three designs, none of them exceeded the yield limit of the materials, the non-splinted model showed more stress on the bone.